2010
DOI: 10.1128/jvi.00731-10
|View full text |Cite
|
Sign up to set email alerts
|

Different Rotavirus Strains Enter MA104 Cells through Different Endocytic Pathways: the Role of Clathrin-Mediated Endocytosis

Abstract: Rotaviruses, the single most important agents of acute severe gastroenteritis in children, are nonenveloped viruses formed by a three-layered capsid that encloses a genome formed by 11 segments of double-stranded RNA. The mechanism of entry of these viruses into the host cell is not well understood. The best-studied strain, RRV, which is sensitive to neuraminidase (NA) treatment of the cells, uses integrins ␣2␤1 and ␣v␤3 and the heat shock protein hsc70 as receptors and enters MA104 cells through a non-clathri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
111
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 62 publications
7
111
1
4
Order By: Relevance
“…Although drugs affecting dynamin and cholesterol have been shown to impair RRV infection (33, 55), drugs and dominant negative mutants known to impair clathrin or caveolin-dependent endocytosis have no inhibitory effects on RRV replication (33, 55). Moreover, conflicting observations have been made about the effects of drugs that block endosomal acidification (8,15,33). There is thus no definitive model of the RV entry process at this time (2,42,54).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although drugs affecting dynamin and cholesterol have been shown to impair RRV infection (33, 55), drugs and dominant negative mutants known to impair clathrin or caveolin-dependent endocytosis have no inhibitory effects on RRV replication (33, 55). Moreover, conflicting observations have been made about the effects of drugs that block endosomal acidification (8,15,33). There is thus no definitive model of the RV entry process at this time (2,42,54).…”
mentioning
confidence: 99%
“…Whether RV behaves like the other nonenveloped viruses during membrane penetration remains controversial. A direct entry of RV particles was initially proposed (26, 39), but more recent studies suggested an endocytosis step during RV entry (8,33,55). Most of the RV entry data were obtained by using the simian rhesus RV (RRV) strain and MA104 cells as a model, but different RV strains appear to use various endocytosis pathways (33).…”
mentioning
confidence: 99%
“…DS-1 and RV-5 rotaviruses differ in only 3 amino acids in VP8*, so it is possible that RV-5 also uses this route. In contrast, these treatments do not affect RRV internalization, which occurs by an endocytic route that may be independent of clathrin and caveola (11,13). The Nar 3 variant of RRV is considered to utilize a clathrin-dependent pathway, possibly due to a single VP8* amino acid change from RRV (Lys187Arg) (12).…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus usage of GM1 shows a possible association with internalization by clathrin-mediated endocytosis (Tables 1 and 2). MA104 cell entry by Wa, DS-1, UK, and TFR-41 is blocked by treatments that inhibit clathrin-mediated endocytosis and alter endosomal pH, suggesting that they utilize a pathway that includes clathrinmediated endocytosis (11,12). UK VP4 is sufficient to direct rotavirus internalization by this pathway (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation